Calc
posted by Chris .
Which expression is equivalent to sin(3x) + sin x?
A.
2cos(2x)sin x
B.
2sin(2x)sin x
C.
2sin(2x)cos x
D.
2sin(2x)cos x
E.
2cos(2x)sin x

I don't know if you came across the identity
sin (3x) = 3sinx  4sin^3 x
so yours:
sin(3x) + sinx = 4sinx  4sin^3 x
= 4sinx(1  sin^2x)
= 4sinx(cos^2x)
= 2(2sinxcosx)(cox) . I just grouped them
= 2(sin(2x) (cosx)
which is D
Respond to this Question
Similar Questions

tigonometry
expres the following as sums and differences of sines or cosines cos8t * sin2t sin(a+b) = sin(a)cos(b) + cos(a)sin(b) replacing by by b and using that cos(b)= cos(b) sin(b)= sin(b) gives: sin(ab) = sin(a)cos(b)  cos(a)sin(b) … 
Ap Calc AB
Determine (dy/dx) using implicit differentiation. cos(X^2Y^2) = x I'm really confused what to do now..i think the next steps are: d/dx [cos(X^2*Y^2)] = d/dx [x] = sin(X^2*Y^2)* ((X^2*2Y dy/dx) + (Y^2*2X)) = 1 = 2YX^2 sin(X^2*Y^2) … 
Math, PreCalc
the original problem was: Solve: sin(3x)sin(x)=cos(2x) so far i've gooten to: sin(x)(2sin(x)cos(x)1)=cos^2(x)sin^2(x) Where would I go from here? 
Precal
I do not understand how to do this problem ((sin^3 A + cos^3 A)/(sin A + cos A) ) = 1  sin A cos A note that all the trig terms are closed right after there A's example sin A cos A = sin (A) cos (A) I wrote it out like this 0 =  … 
trigonometry (please double check this)
Solve the following trig equations. give all the positive values of the angle between 0 degrees and 360 degrees that will satisfy each. give any approximate value to the nearest minute only. 1. sin2ƒÆ = (sqrt 3)/2 2. sin^2ƒÆ = … 
Precalculus
Verify the identities. Cos^2x  sin^2x = 2cos^2x  1 When verifying identities, can I work on both side? 
Precalc/Calc
Which expression is equivalent to sin(3x) + sin x? 
Calc
Which functions of x and y in terms of time t can be derived from this rectangular equation? 
Math
Which expression is equivalent to sin(3x) + sin x? 
another please help me check~calculus maths
y=3e^(2x)cos(2x3) verify that d^2y/dx^24dy/dx+8y=0 plz help me i tried all i could but it become too complicated for me here set u=3e^(2x) v=cos(2x3) du/dx=6e^(2x) i used chain rule dv/dx=2sin(2x3) dy/dx=3e^(2x)sin(2x3)+cos(2x3)6e^(2x) …